Essential oils for COVID-19 management: A systematic review of randomized controlled trials - Duta, Teuku F.; Rizki, Diva R.; Purnama , Agnia; Rademaker, Marius; Wollina, Uwe; Acharya, Yogesh; Abdeen, Ziad; Rosa, Sandro G. V.; Nielsen, Henning B.; Subbaram, Kannan (Narra Sains Indonesia, 2023)
Essential oils can be a beneficial adjuvant therapy in managing coronavirus disease 2019 (COVID-19). This systematic review aims to evaluate the efficacy of essential oils in ameliorative COVID-19-related symptoms. Published studies reporting the efficacy of essential oils as adjuvant therapy for COVID-19 were screened on Scillit, Scopus, SciFinder, and PubMed (December 7th, 2022). Inclusion criteria include the randomized controlled trials (RCTs) participated by those diagnosed with COVID-19 and treated with essential oils as adjuvant therapy. Quality assessment was carried out using Cochrane ‘risk-of-bias’ 2.0 tool. A total of 2112 records were retrieved from the initial screening, which was reduced to four publications (n=344 individuals). The foregoing studies reported that essential oils could improve the recovery rate, alleviate post-COVID-19 fatigue, and prevent disease progression. Regarding their potential antiviral activity, better designed studies are needed. In conclusion, essential oils as adjuvant therapy are beneficial in ameliorating mild COVID-19 symptoms.